2023
DOI: 10.1021/acsnano.3c02948
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Li+ Solvation Structure by a “Bulky Coordinating” Strategy Enables Nonflammable Electrolyte for Ultrahigh Voltage Lithium Metal Batteries

Abstract: In battery electrolyte design principles, tuning Li+ solvation structure is an effective way to connect electrolyte chemistry with interfacial chemistry. Although recent proposed solvation tuning strategies are able to improve battery cyclability, a comprehensive strategy for electrolyte design remains imperative. Here, we report a solvation tuning strategy by utilizing molecular steric effect to create a “bulky coordinating” structure. Based on this strategy, the designed electrolyte generates an inorganic-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 63 publications
(159 reference statements)
0
15
0
Order By: Relevance
“…The presence of 60 % DCE slightly shortened the distances of LiÀ O (SOCl 2 ) and LiÀ Al (AlCl 4 À ) and resulted in a new LiÀ C (DCE) peak at 2.9 Å (Figure 4d). This indicated that DCE molecules were involved in the first layer of the solvation structure that encircled the Li ions and SOCl 2 molecules, [37,38] thus serving as an effective diluent that effectively suppressed the corrosivity of the SOCl 2 -based electrolyte (Figure S14).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The presence of 60 % DCE slightly shortened the distances of LiÀ O (SOCl 2 ) and LiÀ Al (AlCl 4 À ) and resulted in a new LiÀ C (DCE) peak at 2.9 Å (Figure 4d). This indicated that DCE molecules were involved in the first layer of the solvation structure that encircled the Li ions and SOCl 2 molecules, [37,38] thus serving as an effective diluent that effectively suppressed the corrosivity of the SOCl 2 -based electrolyte (Figure S14).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…One routine way is to promote in situ formation of a stable SEI layer by optimizing the electrolytes, including sacrificial additives, highly concentrated electrolytes, and fluorinated electrolytes . Nevertheless, the so-formed SEI continuously grows by constantly consuming the electrolyte solvents, salt anions, or sacrificial additives in the electrolyte, making it difficult to modulate the composition and structure of the SEI. Accordingly, the improvement in cycling stability by using a large excess of electrolyte inevitably compromises the energy density of batteries. Another approach is to replace the electrolyte-derived SEI by ex-situ formed artificial SEI layers such as inorganic materials (for example, Li 3 PO 4 , LiF, Li 2 S), organic polymers (for example, polyrotaxane- co -poly­(acrylic acid) (PR–PAA), P­(St-MaI), polydimethylsiloxane, and copolymer of poly­(ethylene glycol) methyl ether methacrylate and 2-[3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl)­ureido]­ethyl methacrylate), and organic–inorganic composites. However, ionic insulation or poor ionic conductivity would definitely retard the Li + transfer across the interface, resulting in increased polarization and dendrite growth .…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been much work focused on optimizing the electrolyte systems, there are some aspects remaining to be improved. First, the options of the electrolytes are limited, most of which are ester- or ether-based electrolytes with high combustibility.…”
Section: Introductionmentioning
confidence: 99%